THE RELATIONSHIP BETWEEN URBAN LAND USE AND PEDESTRIAN AND CYCLIST CASUALTIES - Priyantha Wedagama, D. M. (Jurnal Ilmiah Teknik Sipil; Vol. 11, No. 1 Januari 2007)
Promoting a modal shift to walking and cycling for shorter journeys as well as making these modes safer has been examined by the UK government, practitioners and academics and researchers. It has been found that urbanisation has the effect of increasing casualties to non-motorised road users. This paper examines the relationship between non-motorised transport casualties (in particular pedestrians and cyclists) and urban land use. The study concentrates on characterising the spatial and temporal variation of non-motorised transport casualties and urban land use. More specifically, this relationship is examined spatially and with respect to day and night, and the weekly variation of working hours. Other associated factors, such as land use proportion, population density and junction density are considered to explain the relationship.
Keywords: pedestrians, cyclists, casualties, urban land use.